Effect of various calcium hydroxide removal protocols on the dislodgement resistance of biodentine in an experimental apexification model - Özgür İlke Ulusoy; Keziban Olcay; Mutahhar Ulusoy (Elsevier, 2021)
Background/purpose: Residual calcium hydroxide (CH) in the root canal dentine walls may influence the adhesion of tricalcium silicate-based materials. The aim of this study is to evaluate the effect of various CH removal protocols on the dislodgement resistance of biodentine from simulated immature root canals in an experimental apexification model. Materials and methods: CH was applied to 120 simulated immature root canals. The samples were divided into 12 experimental groups (n = 10) according to the applied irrigation protocols used for the removal of CH: Group 1: Sodium hypochlorite (NaOCl), Conventional needle irrigation (CNI); Group 2: NaOCl, EndoActivator; Group 3: NaOCl, XP-endo Finisher; Group 4: NaOCl- Ethylenediaminetetraacetic acid (EDTA), CNI; Group 5: NaOCl-EDTA, EndoActivator; Group 6: NaOCl-EDTA, XP-Endo Finisher; Group 7: NaOCl+etidronic acid (HEBP), CNI; Group 8: NaOCl+HEBP, EndoActivator; Group 9: NaOCl+HEBP, XP-endo Finisher; Group 10: NaOCl- Peracetic acid (PAA), CNI; Group 11: NaOCl-PAA, EndoActivator; Group 12: NaOCl-PAA, XP-endo Finisher; Control Group: CH was not applied. Biodentine was placed at the apical thirds of 130 immature root canals. Vertical loading was applied to biodentine fillings inside the dentin discs. Maximum force to dislodge the material was statistically analyzed with ANOVA. Results: The control, NaOCl+HEBP (CNI, EndoActivator, XP-endo Finisher) and NaOCl-PAA (EndoActivator, XP-endo Finisher) groups exhibited the lowest dislodgement resistance values (p < 0.001). When used CNI, irrigation with NaOCl+HEBP resulted in lower resistance to dislodgement of biodentine compared to NaOCl, and NaOCl-EDTA (p < 0.001). Conclusion: Adhesion of apical barrier materials to root canal dentine can be influenced by the irrigation protocols used for CH removal.